Direct link between the characteristics of atmospheric new particle formation and Continental Biosphere-Atmosphere-Cloud-Climate (COBACC) feedback loop - Kulmala, Markku; Cai, Runlong; Ezhova, Ekaterina; Deng, Chenjuan; Stolzenburg, Dominik; Dada, Lubna; Guo, Yishuo; Yan, Chao; Peräkylä, Otso; Lintunen, Anna; Nieminen, Tuomo; Kokkonen, Tom V.; et al. (Finnish Environment Institute, 2024)
We investigated the role of atmospheric new particle formation (NPF) in the Continental Biosphere-Atmosphere-Cloud-Climate (COBACC) feedback mechanism, particularly the We investigated the role of atmospheric new particle formation (NPF) in the Continental Biosphere-Atmosphere-Cloud-Climate (COBACC) feedback mechanism, particularly the influences of NPF on condensation sink and particle number and cloud condensation nuclei (CCN) concentrations. Using atmospheric observations at the SMEAR II station in Hyytiala, Finland, we showed that the growth rates of particles originating from NPF are relatively constant, depending only weakly on low-volatility vapor concentrations and having no apparent connection with the strength of NPF or the level of background pollution. We then constrained aerosol dynamic model simulations with these observations. We showed that under conditions typical for the boreal forest atmosphere, even the weakest NPF with a relatively low particle formation rate of 0.01 cm(-3) s(-1) at 5 nm ( J(5)) is capable of enhancing the condensation sink (CS) to values larger than 0.001 s(-1) after two days of particle growth. When J(5) lies in a typical NPF range between about 0.1 and 0.5 cm(-3) s(-1) at SMEAR II, the growing-mode particles originating from NPF tend to dominate the total CS at this station. Increases in CS associated with NPF further increase the ratio of diffuse radiation to global radiation under clear sky by factors between about 1.5 and 2 at SMEAR II, which boosts the forest gross primary production and enhances forest carbon sink. Furthermore, when J 5 is larger than about 0.1 cm(-3) s(-1), NPF frequently produces particle number concentrations larger than 1000 cm-3 into the size range relevant for cloud droplet activation. We conclude that outside the late autumn and winter periods when the frequency of NPF is low at SMEAR II, NPF followed by subsequent particle growth is able to give a dominant contribution to both CS and CCN concentration - the two most relevant aerosol-related ...